Clinical outcomes and capsular bag stability of a four-point haptic bitoric intraocular lens - Kretz, Florian Tobias Alwin; Breyer, Detlev Richard Hans; Klabe, Karsten; Auffarth, Gerd U.; Kaymak, Hakan (Journal of refractive surgery, 2015)
To evaluate the visual, refractive, and aberrometric outcomes of a bitoric intraocular lens (IOL) and its stability and alignment within the capsular bag.